THE NEED TO INCREASE THE EFFICIENCY OF USING BUDGET FUNDS WHEN CONDUCTING TENDERING UNDER THE CONDITIONS OF THE STATE OF MARTIAL (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article reveals the peculiarities of public procurement in the public finance system of Ukraine; analyzed features of public procurement in Ukraine and their compliance with EU requirements, as well as factors affecting their effectiveness; investigated the problems that exist in Ukraine when conducting tender purchases in wartime conditions; identified ways to overcome shortcomings in conducting public procurement in modern conditions.In the event of Russia's invasion of Ukraine in 2022, our country has suffered significant economic losses, which requires significant budget savings. The 2022 budget was met thanks to the help of foreign partners, but many purchases were canceled due to the redirection of funds for the purchase of weapons and military equipment. The question of increasing the efficiency of the use of budget funds has become more acute than ever, including through the improvement of tender purchases in order to minimize corruption during their implementation. In 2023, the situation in the use of budget funds partially improved, which made it possible to use tender procurement more widely, in particular, in the procurement of food products and property for law enforcement agencies. At the same time, the level of corruption during their implementation did not decrease significantly. This requires a significant reform of tender legislation and improvement of the work of state control structures. In addition, it is important to strengthen the role of the public in conducting public procurement at all levels, including for defense needs. The practice of conducting them in 2022 showed that as soon as public procurement bypassed the Prozorro system, prices for many goods, works and services rose sharply compared to prices on the free market. First of all, this was manifested in the procurement of goods and services by the relevant structures of the Ministry of Defense of Ukraine, which were disguised as "secret". Under the pressure of the public and international sponsors, the Ukrainian authorities were forced to partially open the system of public procurement in this Ministry, but it was not possible to achieve a significant increase in their effectiveness. Therefore, the next step should be a substantial revision of the tender legislation and maximum opening of public procurement materials to the public. Otherwise, Ukraine will not be able to receive significant foreign investments for the reconstruction of the country after the war.
Keywords: public procurement, budget funds, Prozorro system, tender procedure, corruption, financing strategy, financial management, martial law.